Corrosion Inhibitors, Principles and Recent Applications 2018
DOI: 10.5772/intechopen.72753
|View full text |Cite
|
Sign up to set email alerts
|

Green Corrosion Inhibitors, Past, Present, and Future

Abstract: Green corrosion inhibitors are of interest because there has been an increase in environmental awareness and a change in regulations that restrict regular corrosion inhibitors due to their toxicity. Natural products are a good source of green corrosion inhibitors, where most of their extracts containing the necessary elements such as O, C, N, and S, which are active in organic compounds, assist in adsorption of these compounds on metals or alloys to form a film that protects the surface and hinders corrosion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 88 publications
0
28
0
1
Order By: Relevance
“…In Table 1 some examples of green corrosion inhibitors for some species. Green corrosion inhibitors have been positioned as a good alternative because they have come from natural sources, so they are considered less toxic, biodegradables, ecofriendly, and sustainable [1,10,26,38,39].…”
Section: Green Corrosion Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1 some examples of green corrosion inhibitors for some species. Green corrosion inhibitors have been positioned as a good alternative because they have come from natural sources, so they are considered less toxic, biodegradables, ecofriendly, and sustainable [1,10,26,38,39].…”
Section: Green Corrosion Inhibitionmentioning
confidence: 99%
“…Currently, different objects have been built using metals. Unfortunately, the deterioration of metallic materials is impossible to stop or avoid occurring, because the reaction of metallic materials with the present oxygen in any environment is energetically favorable and oxidation occurs spontaneously [1]. Industrially many serious and economic problems are produced for corrosion, it produces material loss on surface, and it conduce that the materials loss their mechanical properties and the structures fail making the industrial process shutting down.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors from plant extracts are characterized by its renewable resources, facilely obtainable, low cost and don't form any harmful effects on the environment [19]. The green corrosion extracts mainly contain the needful elements (such as O, C, N, and S) that help molecules to be adsorbed on the surfaces of metals or alloys to form a film that protects the surface from corroded [20]. In the literature survey, there is no indication to apply this extract as corrosion inhibitor for zinc in HCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of corrosion inhibitors is the most common method applied to protect these metals, the toxicity of regular inhibitors has led to the search for new green corrosion inhibitors, which are mostly obtained from natural products, therefore considered eco-friendly, relatively harmless upon disposal, and where the natural products from the food industry may be valorized. 12 By-products containing organic substances, such as phenolic compounds, alkaloids, and tannins, may be useful as corrosion inhibitors in several corrosive media as they may be adsorbed onto the metal's surface. 13,14 In the case of SCGs, the use of caffeine as an inhibitor has already been tested for different metals and alloys, 15,16 and studies using specifically coffee extracts have shown their efficacy as a corrosion inhibitor for C-steel in a 1 mol L -1 HCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as pH, temperature, sample mass, and extraction time may be studied, as well as sequential steps in order to maximize the extraction. 12,20 In most of the studies concerning the production of eco-friendly corrosion inhibitors extracts, however, the extraction parameters are chosen randomly or based in univariate experiments 17,[21][22][23] . These procedures are time-consuming, and a large number of experiments are generally needed to perform the extraction.…”
Section: Introductionmentioning
confidence: 99%